Hypoxic Conditioning as a New Therapeutic Modality - Verges, Samuel; Chacaroun, Samarmar; Godin-Ribuot, Diane; Baillieul, Sébastien (Frontiers in Pediatrics, 2015)
Preconditioning refers to a procedure by which a single noxious stimulus below the threshold of damage is applied to the tissue in order to increase resistance to the same or even different noxious stimuli given above the threshold of damage. Hypoxic preconditioning relies on complex and active defenses that organisms have developed to counter the adverse consequences of oxygen deprivation. The protection it confers against ischemic attack for instance as well as the underlying biological mechanisms have been extensively investigated in animal models. Based on these data, hypoxic conditioning (consisting in recurrent exposure to hypoxia) has been suggested a potential non-pharmacological therapeutic intervention to enhance some physiological functions in individuals in whom acute or chronic pathological events are anticipated or existing. In addition to healthy subjects, some benefits have been reported in patients with cardiovascular and pulmonary diseases as well as in overweight and obese individuals. Hypoxic conditioning consisting in sessions of intermittent exposure to moderate hypoxia repeated over several weeks may induce hematological, vascular, metabolic and neurological effects. This review addresses the existing evidence regarding the use of hypoxic conditioning as a potential therapeutic modality and emphasizes on many remaining issues to clarify and future researches to be performed in the field.